Design of Information Technology Infrastructure Integration as Support Academic Sevice at a University - Nursandi, Muhammad; Ramadhani, Amanda Putri; Maretmy, Angella; Septian, Daniel Marvelino (LPPM Universitas Sari Mulia, 2025)
The rapid growth of digital academic services requires universities to develop reliable, scalable, and integrated information technology infrastructures. This study focuses on the design and planning of the IT infrastructure for Building E at Universitas Sari Mulia, aiming to support both academic and administrative activities while integrating seamlessly with the existing campus network. The research applies a design and development method, encompassing technical analysis, network architecture design, detailed system design, and conceptual validation. The Building E infrastructure includes six main rooms, with a server room functioning as the central local network management node. A three-tier network architecture core, distribution, and access layers is implemented to ensure efficient management, traffic segmentation, and direct interaction with end users. The integration plan considers inter-building connectivity, network security, and operational workflow to maintain stability and reliability while accommodating future expansion. The proposed design enhances network performance, simplifies maintenance, ensures centralized data management, and provides reliable digital services for students, faculty, and administrative staff. Conceptual validation confirms that the design aligns with technical requirements, security standards, and institutional policies. The study establishes a strategic foundation for developing a smart campus environment, ensuring that Building E contributes significantly to the university’s digital transformation and long-term academic excellence.